The relationship between English and European Community administrative law: the principles of legitimate expectations and proportionality - Thomas, Robert (1998)
This thesis concerns the relationship between English and European Community administrative law. The main aim is to draw out the nature of this relationship by comparing the development of two principles, the principles of legitimate expectations and proportionality, within English and European Community administrative law. A secondary aim is to assess the challenge presented by European Community law for English law. The emphasis is on the distinct visions of law or legal traditions which have influenced both systems of administrative law rather than specific substantive laws. Chapter 2 identifies the nature of the English and Continental traditions of administrative law and the development of English and European Community administrative law. More specifically, English law is based on the common law approach while Continental and European Community administrative law has a more purposive orientation. Chapter 3 examines the pressures for the adoption of the two principles in English law. These pressures have been both internal, through the role of Lord Diplock, and external, through the influence of European Community law. In Chapters 4, 5, 6 and 7 the principles are examined in depth in both European Community and English administrative law. Comparative observations of the articulation of the principles in European Community law and their development in English law are made in chapters 5 and 7. In this respect the identification of the different traditions of administrative law becomes crucial in assessing the success of the principles as legal transplants in English law. The conclusion draws together these themes in order to identify the relationship between English and European Community law. An assessment is also made of the challenge presented by European Community law and suggestions are made as to what English law ought to do in order to respond effectively.